2011
DOI: 10.1021/ma201119u
|View full text |Cite
|
Sign up to set email alerts
|

Normally Oriented Cylindrical Nanostructures in Amphiphilic PEO–LC Diblock Copolymers Films

Abstract: The amphiphilic diblock copolymers consist of poly(ethylene oxide) (PEO) and poly(methacrylate) (PMA) having azobenzenes as mesogen units in the side chain afford highly ordered phase-segregated nanostructures, in which PEO cylindrical domains are hexagonally arranged and normally oriented in PMA matrix in the thin films. The liquid crystalline ordering in the strongly segregated block copolymers plays one of the most important roles to attain such an excellent arrangement of the nanostructure, potentially lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
82
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(95 citation statements)
references
References 95 publications
13
82
0
Order By: Relevance
“…Although some types of polymers with BA moieties have been synthesized, the photoreaction and SR formation in photoreactive polymers comprised of BA-derivative side groups have yet to be attained. [23][24][25] In this context, herein we first demonstrate that a new photosensitive polymer comprised of 4-methoxy-N-benzylideneaniline side groups (P1, Fig. 1(a)), which is transparent in the visible region, realizes a sufficient photoinduced reorientation and SR formation by LP-313-nm light, and intensity and polarization holographies with a 325-nm He-Cd laser, respectively.…”
mentioning
confidence: 86%
“…Although some types of polymers with BA moieties have been synthesized, the photoreaction and SR formation in photoreactive polymers comprised of BA-derivative side groups have yet to be attained. [23][24][25] In this context, herein we first demonstrate that a new photosensitive polymer comprised of 4-methoxy-N-benzylideneaniline side groups (P1, Fig. 1(a)), which is transparent in the visible region, realizes a sufficient photoinduced reorientation and SR formation by LP-313-nm light, and intensity and polarization holographies with a 325-nm He-Cd laser, respectively.…”
mentioning
confidence: 86%
“…The homeotropic anchoring of rodlike LC molecules at the free surface has been predicted by theoretical considerations, [10,20] and experimental observations of side-chain LC polymer thin films are in agreement with this. [21] When the free surface is covered with a segregated layer, the excluded volume effect from the plane solid substrate should dominate. [22] An alternative explanation can be the tendency to adopt a planar orientation of the mesogenic groups in the segregated PBMA-b-PAz.…”
mentioning
confidence: 99%
“…In addition, the number-average molecular weight of the polymer was M n = 19,000 (48 oligothiophene monomer units) with the polydispersity index (M w /M n , PDI) of 1.21 as measured by GPC (Figure 4). Asaoka et al reported that amphiphilic block copolymers consisting PEO and poly(methacrylate) with azobenzene derivatives in the side chain (PEO-b-PAzMAs) afford highly ordered nano-phase-separated structures, in which their PDIs were 1.07-1.36 [15]. PEO-b-PAzMAs exhibit hexagonally arranged dot patterns with a diameter of 3 nm over the whole surface as observed by AFM.…”
Section: Resultsmentioning
confidence: 99%
“…The product obtained was purified by column chromatography (silica gel, CH 2 Cl 2 ) to give 14 (orange solid; 0.929 g, 1.58 mmol, 52 %) 1. H NMR (500 MHz, CDCl 3 ): δ/ppm = 7.14 (d, 1H), 7.10 (d, 1H), 7.07 (d, 1H), 7.05 (d, 1H), 7.01 (d, 1H), 6.98 (d, 1H), 6.92 (d, 1H), 6.70 (d, 1H), 4.58 (t, 1H), 3.88-3.84 (m, 1H), 3.80-3.75 (m, 1H), 3.53-3.49 (m, 1H), 3.44-3.40 (m, 1H), 2.85 (t, 2H), 1.85-1.51 (m, 10H).Tetrahydro-2-(4-{5-[2-(5-{5 -[2-(5-butyl-2-thienyl)ethynyl]-2,2 :5 ,2 -terthiophene}-yl)ethynyl]-2-thienyl}butoxy)-2H-pyran(15). Prepared similarly to 9 from 14 (0.901 g, 1.53 mmol), PdCl 2 (PPh 3 ) 2 (37.4 mg, 53.3 μmol, 3.5 mol%), CuI (11.3 mg, 59.3 μmol, 3.9 mol%), 4 (0.374 g, 2.28 mmol, 1.5 eq.)…”
mentioning
confidence: 99%